Search for neutral higgs bosons decaying to tau pairs in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
A search for the production of neutral Higgs bosons Φ decaying into τ+τ- final states in pp̄ collisions at a center-of-mass energy of 1.96 TeV is presented. The data, corresponding to an integrated luminosity of approximately 325pb-1, were collected by the D0 experiment at the Fermilab Tevatron Collider. Since no excess compared to the expectation from standard model processes is found, limits on the production cross section times branching ratio are set. The results are combined with those obtained from the D0 search for Φb(b̄)→bb̄b(b̄) and are interpreted in the minimal supersymmetric standard model. © 2006 The American Physical Society.